Results of the Monitoring for BCG Vaccination Complications - S.M. Liepshina; L.V. Skripka; Ye.V. Tishchenko; N.S. Skripka; Ye.I. Yurovskaia (Zaslavsky O.Yu., 2015)
BCG vaccination remains relevant because of the tense epidemiological situation on tuberculosis in Ukraine. BCG vaccines are safe, but when they are used, there is a risk of complications. In the Donetsk region, from 2004 to 2008 the proportion of complications after immunization did not exceed 0.09 %, from 2008 to 2012 their growth was marked up to 0.6 %. It was found that it was associated with the use of BCG vaccine manufactured by Statens Serum Institut (Denmark). In 2008, cases of BCG-induced osteitis on BCG and BCG-M vaccine (strain BCG-1, Russian Federation) were detected firstly in the region, earlier such cases were considered as bone tuberculosis.